2013
DOI: 10.1088/1742-6596/414/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Laser surface modification of polyethersulfone films: effect of laser wavelength on biocompatibility

Abstract: In this paper laser ablation of polyethersulfone (PES) films regarding to the change in biocompatibility of the surface is investigated at 3 different wavelengths of 193nm (ArF), 248 nm (KrF) and 308 nm (XeCl). The optimum laser fluence and number of pulses for the improvement of the surface biocompatibility is found by examination of the surface behavior in contact with platelets and fibroblasts cells at 3 wavelengths. These biological modifications are explained by alteration of the surface morphology and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The pulse duration effect has also been studied with reported structures appearing with pulses in the ns, ps and fs regime [385,388,389]. Furthermore, it has been reported that their shape also varies depending on the wavelength of the incident pulses as well as the incidence angle [387,390]. The formation of such structures has been exploited to tailor a variety of material properties derived from surface topography.…”
Section: Microspikes and Hierarchical Structuresmentioning
confidence: 99%
“…The pulse duration effect has also been studied with reported structures appearing with pulses in the ns, ps and fs regime [385,388,389]. Furthermore, it has been reported that their shape also varies depending on the wavelength of the incident pulses as well as the incidence angle [387,390]. The formation of such structures has been exploited to tailor a variety of material properties derived from surface topography.…”
Section: Microspikes and Hierarchical Structuresmentioning
confidence: 99%